Adapting fragmentation: changing borders in Olive Kitteridge (HBO 2014); Case Histories, (BBC 2011-2013); Love and Friendship (2016) and Sanditon (ITV 2019) - Armelle Parey (Interfaces)
Text and film are typically framed by liminal spaces or borders where the reader or viewer enters or leaves the narrative world. Some novels, however, do not possess these traditional borders. Endings may be missing. Such is the case of unfinished novels interrupted by their author's death. Conversely, borders may be multiple when the text is fragmentary, i.e. made up of several others, as in an epistolary novel devoid of a unifying voice or a short-story cycle which multiplies (intermediary) borders. What happens when these texts are adapted to the screen? The questions pursued in this paper are to what extent and with what effects the borders of the text are set up or renegotiated when a fragment or a partially fragmentary text is adapted to the screen in formats that usually deliver narrative wholes and completed stories.We shall first look at how fragmentation may be smoothed out to merge into a more comfortable whole that fits into a genre through the example of two TV mini-series based on diversely fragmentary source texts, one being a short-story cycle and the other a novel-sequence (Olive Kitteridge, HBO 2014; Case Histories, BBC 2011-2013). Secondly, considering two adaptations of Jane Austen's early Lady Susan and the unfinished Sanditon, which do not deliver the usual romantic happy ending, we shall see how changing the borders can also free adaptation from a (sub)genre and fixed expectations (Love and Friendship by Whit Stillmann, 2016 and Sanditon, ITV 2019).